2020
DOI: 10.1017/s0007114520002743
|View full text |Cite
|
Sign up to set email alerts
|

Kefir microbial composition is a deciding factor in the physiological impact of kefir in a mouse model of obesity

Abstract: Kefir consumption has been demonstrated to improve lipid and cholesterol metabolism, however our previous study identified that benefits vary between different commercial and traditional kefir. Here, we investigate the ability of pitched culture kefir, i.e., kefir produced by a small number of specific strains, to recapitulate health benefits of a traditional kefir, in a diet induced obesity mouse model, and examine how microbial composition of kefir impacts these benefits. Eight week old female C57BL/6 mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Kefir, a fermented milk-based dairy product, has recently been recognized as a beverage with functional characteristics [6][7][8]. Within the past few years, kefir has gained wide consumer acceptance in Europe and in Italy, aided by its image as a 'healthy' food.…”
Section: Introductionmentioning
confidence: 99%
“…Kefir, a fermented milk-based dairy product, has recently been recognized as a beverage with functional characteristics [6][7][8]. Within the past few years, kefir has gained wide consumer acceptance in Europe and in Italy, aided by its image as a 'healthy' food.…”
Section: Introductionmentioning
confidence: 99%
“…lactis , boosting their global benefits [ 159 ] Kefir is a fermented milk that comes from kefir grains, which include a specific and complex mixture of lactic acid and acetic acid bacteria that appears in symbiosis with lactose-fermenting and nonfermenting yeast [ 160 ]. Interestingly, kefir without bacteria or yeast in its composition seems to critically limit the benefits from this product [ 161 ]. Prior works have demonstrated that 3 weeks with daily consumption of probiotic yogurt improved the mood of those whose mood was initially poor [ 162 ].…”
Section: Translational Opportunities: Clinical Management Of Mdd Thro...mentioning
confidence: 99%
“…Kefir in particular is gaining popularity, largely due to an increased appreciation of the potential health benefits. Benefits that have been attributed to specific kefirs include anti-cancer ( de Moreno de LeBlanc et al, 2006 ; Maalouf et al, 2011 ), immunomodulatory ( Vinderola et al, 2005 ; Lee et al, 2007 ), cholesterol lowering ( Bourrie et al, 2018 , 2021 ), and other metabolic health improvements ( Al-Shemmari et al, 2018 ; Ghizi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%